Use the Distributive Property and simplify the expression. 4 + 2(3x – 1) + 9
A.
3x + 14
B.
6x + 11
C.
5x + 14
D.
6x + 15

Question

Asked 10/7/2013 4:04:47 PM

Updated 10/7/2013 5:51:59 PM

1 Answer/Comment

Flagged by debnjerry

Rating

3

4 + 2(3x – 1) + 9

= 4 + 6x - 2 + 9

= 6x + 11

= 4 + 6x - 2 + 9

= 6x + 11

Added 10/7/2013 5:51:59 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/10/2014 1:31:56 PM]

27,106,684

questions answered

There are no comments.